2020
DOI: 10.21134/rpcna.2020.mon.2037
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of COVID-19 pandemic in Spanish adolescents: risk and protective factors of emotional symptoms

Abstract: The psychological impact of the COVID-19 pandemic on children and adolescents is one of the most prevalent concerns all over the world. Adolescence is a developmental stage of high vulnerability due to the challenges this period entails. Additionally, the health emergency crisis has put adolescents even more at risk of developing mental health problems. The present study aims to examine the influence of socio-demographic and COVID-19 related variables on symptoms of depression, anxiety and stress in adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 0 publications
2
29
1
7
Order By: Relevance
“…These results differ to those found in research of general population which highlight that girls generally present higher levels of anxiety, depression, and stress ( Duan et al, 2020 ; Tamarit et al, 2020 ; Zhou et al, 2020 ; Carrillo-López et al, 2021 ; Gilsbach et al, 2021 ; Panchal et al, 2021 ). Therefore, it is necessary to delve further into what factors could influence these results in future research.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…These results differ to those found in research of general population which highlight that girls generally present higher levels of anxiety, depression, and stress ( Duan et al, 2020 ; Tamarit et al, 2020 ; Zhou et al, 2020 ; Carrillo-López et al, 2021 ; Gilsbach et al, 2021 ; Panchal et al, 2021 ). Therefore, it is necessary to delve further into what factors could influence these results in future research.…”
Section: Discussioncontrasting
confidence: 95%
“…Some studies have reported sex differences; highlighting that girls generally have higher levels of anxiety, depression, and stress than boys ( Duan et al, 2020 ; Tamarit et al, 2020 ; Zhou et al, 2020 ; Carrillo-López et al, 2021 ; Gilsbach et al, 2021 ), aspects confirmed by the systematic review by Panchal et al (2021) .…”
Section: Introductionmentioning
confidence: 89%
“…Emerging evidence indicates that adolescent girls are disproportionately affected by the pandemic compared to adolescent boys. This is in part due to higher levels of pre-existing psychopathology in women as well as gender differences in fear processing and presenting higher levels of fear, tension, and confusion compared to boys during the pandemic [ 7 , 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…En el presente estudio, los y las profesionales han observado dificultades asociadas al impacto de las condiciones del entorno físico, en el que se ha vivido durante el confinamiento, en el bienestar de los niños, niñas y adolescentes que participan en sus servicios, aunque se desconoce su alcance. Existen más evidencias que indican que el tiempo en situación de confinamiento (Erades y Morales, 2020;Gómez-Becerra et al, 2020), y las condiciones del entorno físico en que se ha desarrollado el confinamiento (Tamarit et al, 2020) han resultado ser un factor determinante del bienestar. Los niños, niñas y adolescentes que viven en hogares con menor espacio o con un mayor número de personas son más propensos a sufrir estrés y ansiedad.…”
Section: Discussionunclassified